2000
DOI: 10.1515/jpem.2000.13.7.923
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Insulin Resistance Index are Not Independent Determinants for the Variation in Leptin in Obese Children and Adolescents

Abstract: Recent findings have questioned the independent influence of insulin on leptin. We studied whether insulin contributes to leptin in obese children, independent of confounding parameters, such as total adiposity, fasting insulin resistance index, and fat free mass. In 100 obese boys and 103 obese girls, blood levels of leptin, insulin, glucose, and triglycerides were determined. The fasting insulin resistance index (FIRI) was calculated, and body composition was assessed by means of impedance. Leptin and glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
4
7
0
2
Order By: Relevance
“…Our observation of a positive correlation between plasma leptin levels and IGF-1 in children with short stature complements previous studies in prepubertal [31] and peripubertal [32] children and in children with severe malnutrition [33]. As it has been demonstrated that body fat mass is a main determinant for plasma leptin levels [4,5,19,28,34] and IGF-1 is positively correlated with nutritional status [23,35], the close relationship between plasma leptin levels and IGF-1 can be explained. This finding is supported by our data demonstrating higher IGF-1 levels in patients with higher BMI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our observation of a positive correlation between plasma leptin levels and IGF-1 in children with short stature complements previous studies in prepubertal [31] and peripubertal [32] children and in children with severe malnutrition [33]. As it has been demonstrated that body fat mass is a main determinant for plasma leptin levels [4,5,19,28,34] and IGF-1 is positively correlated with nutritional status [23,35], the close relationship between plasma leptin levels and IGF-1 can be explained. This finding is supported by our data demonstrating higher IGF-1 levels in patients with higher BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Since the discovery of leptin, the understanding of its physiological role has evolved from a satiety signal to that of an integrative hormone that responds to and regulates different endocrine pathways with direct metabolic effects on peripheral tissues [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting results are published about the dependent versus independent associations between body fatness, leptin levels, and insulin resistance in obese children. [5153] A clearer understanding of the leptin-obesity–insulin resistance relationship is still required during childhood and adolescence relative to the development of risk factors and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The association of hypertension with hyperinsulinemia was documented in some (18) but not all studies (19). Controversies also exist regarding an association between hypertension and leptin levels (20)(21)(22)(23)(24)(25)(26)(27)). …”
Section: Discussionmentioning
confidence: 99%
“…An association between hyperleptinemia and hypertension has been found in obese subjects at risk for metabolic syndrome (2,8,(27)(28)(29). Most studies regarding the involvement of hormonal factors in the genesis of hypertension include obese subjects.…”
Section: Discussionmentioning
confidence: 99%